Isometric Strength Measures are Superior to the Timed Up and Go Test for Fall Prediction in Older Adults: Results from a Prospective Cohort Study - Valenzuela PL; Maffiuletti NA; Saner H; Schütz N; Rudin B; Nef T; Urwyler P (Clinical Interventions in Aging, 2020)
Pedro L Valenzuela,1 Nicola A Maffiuletti,2 Hugo Saner,3,4 Narayan Schütz,4 Beatrice Rudin,5 Tobias Nef,6 Prabitha Urwyler4,6,7 1Department of Systems Biology, University of Alcalá, Madrid, Spain; 2Human Performance Lab, Schulthess Clinic, Zurich, Switzerland; 3Institute for Social and Preventive Medicine, University of Bern, Bern, Switzerland; 4Gerontechnology & Rehabilitation Group, University of Bern, Bern, Switzerland; 5Höhere Fachschule Pflege, Berufsbildungszentrum Olten, Olten, Switzerland; 6ARTORG Center for Biomedical Engineering Research, University of Bern, Bern, Switzerland; 7Department of Neurology, University Neurorehabilitation Unit, University Hospital Inselspital, Bern, SwitzerlandCorrespondence: Prabitha UrwylerUniversity of Bern, ARTORG Center for Biomedical Engineering Research, Murtenstrasse 50, Bern 3008, SwitzerlandTel +41 31 632 76 07Email prabitha.urwyler@artorg.unibe.chBackground: Isometric strength measures and timed up and go (TUG) tests are both recognized as valuable tools for fall prediction in older adults. However, results from direct comparison of these two tests are lacking. We aimed to assess the potential of isometric strength measures and the different modalities of the TUG test to detect individuals at risk of falling.Methods: This is a prospective cohort study including 24 community-dwelling older adults (≥ 65 years, 19 females, 88± 7 years). Participants performed three variations of the TUG test (standard, counting and holding a full cup) and three isometric strength tests (handgrip, knee extension and hip flexion) at several time points (at baseline and every ∼ 6 weeks) during a one-year follow-up. The association between these tests and the incidence of falls during the follow-up was assessed.Results: Twelve participants out of 24 participants experienced falls during the follow-up. Fallers showed a significantly lower handgrip strength (− 5.7 kg, 95% confidence interval: − 10.4 to − 1.1, p=0.019) and knee extension strength (− 4.9 kg, − 9.6 to − 0.2, p=0.042) at follow-up, while no significant differences were found for any TUG variation.Conclusions: Handgrip and knee extension strength measures – particularly when assessed regularly over time – have the potential to serve as a simple and easy tool for detecting individuals at risk of falling as compared to functional mobility measures (ie, TUG test).Keywords: functional assessment, geriatrics, elderly, physical performance, muscle strength, sarcopenia